Myosin XVI Regulates Actin Cytoskeleton Dynamics in Dendritic Spines of Purkinje Cells and Affects Presynaptic Organization - Roesler, Mona Katrin; Lombino, Franco Luis; Freitag, Sandra; Schweizer, Michaela; Hermans-Borgmeyer, Irm; Schwarz, Jürgen R.; Kneussel, Matthias; Wagner, Wolfgang (Frontiers in Cellular Neuroscience, 2019)
The actin cytoskeleton is crucial for function and morphology of neuronal synapses. Moreover, altered regulation of the neuronal actin cytoskeleton has been implicated in neuropsychiatric diseases such as autism spectrum disorder (ASD). Myosin XVI is a neuronally expressed unconventional myosin known to bind the WAVE regulatory complex (WRC), a regulator of filamentous actin (F-actin) polymerization. Notably, the gene encoding the myosin's heavy chain (MYO16) shows genetic association with neuropsychiatric disorders including ASD. Here, we investigated whether myosin XVI plays a role for actin cytoskeleton regulation in the dendritic spines of cerebellar Purkinje cells, a neuronal cell type crucial for motor learning, social cognition and vocalization. We provide evidence that both myosin XVI and the WRC component WAVE1 localize to Purkinje cell spines. Fluorescence recovery after photobleaching analysis of GFP-actin in cultured Purkinje cells shows that Myo16 knockout as well as Purkinje cell-specific Myo16 knockdown, lead to faster F-actin turnover in the dendritic spines of Purkinje cells. We also detect accelerated F-actin turnover upon interference with the WRC, and upon inhibition of Arp2/3 that drives formation of branched F-actin downstream of the WRC. In contrast, inhibition of formins that are responsible for polymerization of linear actin filaments does not cause faster F-actin turnover. Together, our data establish myosin XVI as a regulator of the postsynaptic actin cytoskeleton and suggest that it is an upstream activator of the WRC-Arp2/3 pathway in Purkinje cell spines. Furthermore, ultra-structural and electrophysiological analyses of Myo16 knockout cerebellum reveals the presence of reduced numbers of synaptic vesicles at presynaptic terminals in the absence of the myosin. Therefore, we here define myosin XVI as an F-actin regulator important for presynaptic organization in the cerebellum.